PENGARUH METODE PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR PKN KELAS III SD NEGERI 091254 BATU ONOM - Sartika Ayunda Sinaga; Natalia Purba; Melvin Simanjuntak (JOURNAL SAINS STUDENT RESEARCH, 2024)
Sartika Ayunda Sinaga, 2024. The Influence of Inquiry Learning on PKN Learning Outcomes at State Elementary School 091254 Batu Onom. Thesis. Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, HKBP Nommensen Pematangsiantar University. Supervisor I Dr. Natalina Purba, S.Sos., M.Pd. and Supervisor II Pdt. Melvin M. Simanjuntak, S.Th., M.Si.This research is classified as experimental research with a quantitative approach by trying to describe the influence of inquiry learning on Civics learning outcomes for class III at SD Negeri 091254 Batu Onom. The subjects of this research were class III students at SD Negeri 091254 Batu Onom, totaling 23 students consisting of 13 boys and 10 girls in the even semester of the 2023/2024 academic year. During three meetings. Data collection on student learning outcomes was carried out using an initial test (Pretest) and final test (Posttest) after the inquiry learning method was carried out.From the results of data processing above, the Pretest Question scores obtained an average score of 53.26 while the post-test learning outcomes score was 89.22. It can be concluded that Inquiry Learning has an influence on PKN Class III learning outcomes at SD Negeri 091254 Batu Onom.